The role of types of administrative skills in achieving the requirements of electronic management: An exploratory study of the opinions of a sample of individuals working at the University of Duhok - Mohammed, Shan (Humanities Journal of University of Zakho, 2021)
This research aims to determine the role of types of administrative skills in achieving the requirements of electronic management, and the higher education sector was identified as a field to conduct the practical side, and the research was based on a set of main and sub hypotheses that were field tested at the University of Duhok, and the research included (53) individuals working at the university The data were collected based on the questionnaire form prepared for this purpose, and the data were analyzed using a set of statistical methods in the program (SPSS V.22) to analyze the correlation and effect relationship between the research variables. The outcome of the research was the arrival of a number of conclusions, the most important of which is the existence of a positive moral correlation between the types of administrative skills and electronic management, as well as the presence of a moral effect for the types of administrative skills in electronic management. Participation in seminars and internal and external conferences..